2016
DOI: 10.1177/0003702815620127
|View full text |Cite|
|
Sign up to set email alerts
|

Application of Raman Spectroscopy and Infrared Spectroscopy in the Identification of Breast Cancer

Abstract: Raman spectroscopy and infrared (IR) spectroscopy are both techniques that allow for the investigation of vibrating chemical particles. These techniques provide information not only about chemical particles through the identification of functional groups and spectral analysis of so-called "fingerprints", these methods allow for the qualitative and quantitative analyses of chemical substances in the sample. Both of these spectral techniques are frequently being used in biology and medicine in diagnosing illness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 46 publications
2
76
0
1
Order By: Relevance
“…healthy breast tissue, cancerous breast tissue, and post-chemotherapy breast tissue). Our key finding was the correlation between the spectral characteristics and treatment efficacy14, which agreed well to one another suggesting that the key to the treatment response was in fact changes in biochemical makeups occurred in the tissue, which could be detected by FTIR and multivariate data analysis approach. We also found that, based on the observed FTIR spectral features, embedding biological tissue in paraffin did not alter chemical information in the analyzed materials, and hence was a suitable sample preparation for FTIR measurement15.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…healthy breast tissue, cancerous breast tissue, and post-chemotherapy breast tissue). Our key finding was the correlation between the spectral characteristics and treatment efficacy14, which agreed well to one another suggesting that the key to the treatment response was in fact changes in biochemical makeups occurred in the tissue, which could be detected by FTIR and multivariate data analysis approach. We also found that, based on the observed FTIR spectral features, embedding biological tissue in paraffin did not alter chemical information in the analyzed materials, and hence was a suitable sample preparation for FTIR measurement15.…”
Section: Discussionsupporting
confidence: 79%
“…Accordingly, the spectral features within these two ranges contained biological bands of interest that were not subject to the interference from the paraffin used as an embedding agent. The detailed assignment of bands found in the spectra of the breast tissue in this study is based mainly on our previous FTIR studies of breast tissue1415 as well as live marine microorganism16.…”
Section: Resultsmentioning
confidence: 99%
“…Once a mass is found in the breast, ultrasonography, diagnostic mammography, and/or magnetic resonance imaging (MRI) will be recommended by a physician. If the mass is possibly malignant, a core needle biopsy and histopathological techniques are necessary [2]. Unfortunately, this invasive examination cannot ensure a 100% correct diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been extensively applied to detect cancers in a wide range of organs including the cervix, skin, mouth, brain, prostate and ear [14,15,16,17,18,19,20,21,22]. Many studies have been published in the last decade using Raman spectroscopy as a non-invasive tool for the diagnostic analysis of breast cancer cells and tissues [23,24,25,26,27,28,29,30], where differences between cancerous samples and normal samples have been analyzed and explained. The present work has been undertaken to understand the progression of breast cancer by monitoring different phases of cancer systematically, which could suggest potential biomarkers of cancer progression and could be used for early detection.…”
Section: Introductionmentioning
confidence: 99%